2013
DOI: 10.1097/wnr.0b013e3283629195
|View full text |Cite
|
Sign up to set email alerts
|

Minocycline improves postoperative cognitive impairment in aged mice by inhibiting astrocytic activation

Abstract: Astrocytes are proving to be critical for the development of cognitive functions. In addition, astrocytic activation contributes toward cognitive impairment induced by chronic cerebral hypoperfusion. Minocycline has been shown to exhibit long-term neuroprotective effects in vascular cognitive impairment rat models through the inhibition of astrogliosis, and has shown potential for the prevention and treatment of postoperative cognitive decline in elderly patients. This study aimed to examine the effect of mino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 23 publications
1
11
0
Order By: Relevance
“…During aging, microglia and astrocytes, the two major cell effectors contribute to chronic activation of neuroinflammation, overexpression of proinflammatory cytokines, and reactive oxygen species. Animal studies show that inhibiting astrocytic activation using antiinflammatory minocycline can alleviate the hepatectomy-related long-term impairment of spatial memory in 19-month-old C57BL/6 mice (Jin et al 2014) and improves cognitive impairment in AD models (Choi et al 2007). Astrocytes become highly reactive in response to neuroinflammation, and the activation of astrocytes is characterized by hypertrophy and cell proliferation, which is associated with GFAP hyper-expression (Eng et al 2000).…”
Section: Discussionmentioning
confidence: 99%
“…During aging, microglia and astrocytes, the two major cell effectors contribute to chronic activation of neuroinflammation, overexpression of proinflammatory cytokines, and reactive oxygen species. Animal studies show that inhibiting astrocytic activation using antiinflammatory minocycline can alleviate the hepatectomy-related long-term impairment of spatial memory in 19-month-old C57BL/6 mice (Jin et al 2014) and improves cognitive impairment in AD models (Choi et al 2007). Astrocytes become highly reactive in response to neuroinflammation, and the activation of astrocytes is characterized by hypertrophy and cell proliferation, which is associated with GFAP hyper-expression (Eng et al 2000).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, both LPS and minocycline affect astrocytic function in vitro and in vivo [6569]. Furthermore, LPS is known to drive infiltration of monocytes and neutrophils into the brain parenchyma [70].…”
Section: Regulation Of Adult Hippocampal Neurogenesis By Inflammationmentioning
confidence: 99%
“…In studies of CIPN, minocycline prevented CIPN-related symptoms and the activation of astrocytes despite the lack of microglial activation indicators [16][17][18][19] . Nevertheless, minocycline also possesses neuroprotective roles [20,28,45,46] . One notable characteristic of minocycline is that it has a direct effect on sodium channels in primary afferent neurons [47] , which suggests it has a role of peripheral analgesia.…”
Section: Bcp Induced By Walker 256 Mammary Carcinoma Cell Inocula Tionmentioning
confidence: 99%
“…However, accumulating evidence indicates that it prevents chemotherapy-induced peripheral neuropathy (CIPN) via the inhibition of astrocytes [16][17][18][19] . Moreover, it has also been demonstrated that minocycline down-regulates NF-κB activity in several other cell lines [20,21] . Whether minocycline alleviates BCP by inhibiting NF-κB in spinal astrocytes has not been fully explored and understood.…”
Section: Introductionmentioning
confidence: 95%